Foreign Direct Investment in Nepal’s Hydropower Development - Gangol, Pradeep (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
The fund for Foreign Direct Investment (FDI) is globally limited and overstretched. Therefore, Nepal needs to go the extra mile in offering a competitive investment environment to attract FDI flows into Nepal’s hydropower development. It literally means that our investment policies and laws should be more competitive compared to that of other countries like Vietnam, Cambodia and Bangladesh etc.DOI: http://dx.doi.org/10.3126/hn.v14i0.11256HYDRO Nepal JournalJournal of Water, Energy and EnvironmentVolume: 14, 2014, JanuaryPage: 41-42